TRAP1 Chaperones the Metabolic Switch in Cancer - Laura A. Wengert; Sarah J. Backe; Dimitra Bourboulia; Mehdi Mollapour; Mark R. Woodford (Biomolecules, 2022)
Mitochondrial function is dependent on molecular chaperones, primarily due to their necessity in the formation of respiratory complexes and clearance of misfolded proteins. Heat shock proteins (Hsps) are a subset of molecular chaperones that function in all subcellular compartments, both constitutively and in response to stress. The Hsp90 chaperone TNF-receptor-associated protein-1 (TRAP1) is primarily localized to the mitochondria and controls both cellular metabolic reprogramming and mitochondrial apoptosis. TRAP1 upregulation facilitates the growth and progression of many cancers by promoting glycolytic metabolism and antagonizing the mitochondrial permeability transition that precedes multiple cell death pathways. TRAP1 attenuation induces apoptosis in cellular models of cancer, identifying TRAP1 as a potential therapeutic target in cancer. Similar to cytosolic Hsp90 proteins, TRAP1 is also subject to post-translational modifications (PTM) that regulate its function and mediate its impact on downstream effectors, or ‘clients’. However, few effectors have been identified to date. Here, we will discuss the consequence of TRAP1 deregulation in cancer and the impact of post-translational modification on the known functions of TRAP1.